An SNP-dependent cancer-testis antigenic epitope serves as a promising immunotherapeutic target for cancer - Kenji Murata; Tomoyuki Minowa; Tomohide Tsukahara; Taku Yoshida; Akiko Minami; Munehide Nakatsugawa; Yuka Mizue; Aiko Murai; Serina Tokita; Kenta Sasaki; Hisashi Uhara; Terufumi Kubo; et al. (OncoImmunology)
T cells recognize peptides presented by human leukocyte antigen molecules on the cell surface, enabling the immune surveillance of pathological conditions such as cancer. Cancer-testis (CT) antigens are promising targets for cancer immunotherapy because of their restricted expression in normal tissues. In this study, we performed antigen screening of T cell receptors isolated from tumor-infiltrating lymphocytes (TILs) in acral melanoma, using cDNA expression cloning and identified a novel CT antigenic epitope encoded by MAGE-A6 with a single nucleotide polymorphism (SNP). This SNP conferred immunogenicity to the epitope, eliciting a robust immune response against tumor cells. While antigen identification has increasingly relied on reverse immunology approaches using reference sequences that do not contain SNPs, forward immunology approaches, such as cDNA expression cloning, directly identify antigens recognized by T cells exhibiting immune responses, enabling the detection of SNP-derived epitopes. Furthermore, in hot tumors such as acral melanoma that are characterized by a low tumor mutational burden, but high TIL infiltration, TILs predominantly respond to shared antigens with high immunogenicity. These findings underscore the utility of forward immunology in antigen discovery and highlight the potential of SNP-dependent tumor antigens in cancer immunotherapy.